Low temperature circulating fluidized bed gasification and co-gasification of municipal sewage sludge. Part 1: Process performance and gas product characterization. (August 2017) - Thomsen, Tobias Pape; Sárossy, Zsuzsa; Gøbel, Benny; Stoholm, Peder; Ahrenfeldt, Jesper; Frandsen, Flemming Jappe; Henriksen, Ulrik Birk
Graphical abstract: Highlights: Thermal gasification and co-gasification of sewage sludge and wheat straw is tested. Two Low-Temperature-Circulating-Fluidized-Bed gasifiers (100 kW and 6 MW) are used. Influence of fuel composition on process performance and gas quality is examined. Analysis includes gas composition, mass- and energy balance and hot gas efficiency. Abstract: Results from five experimental campaigns with Low Temperature Circulating Fluidized Bed (LT-CFB) gasification of straw and/or municipal sewage sludge (MSS) from three different Danish municipal waste water treatment plants in pilot and demonstration scale are analyzed and compared. The gasification process is characterized with respect to process stability, process performance and gas product characteristics. All experimental campaigns were conducted at maximum temperatures below 750 °C, with air equivalence ratios around 0.12 and with pure silica sand as start-up bed material. A total of 8600 kg of MSS dry matter was gasified during 133 h of operation. The average thermal loads during the five experiments were 62–100% of nominal capacity. The short term stability of all campaigns was excellent, but gasification of dry MSS lead to substantial accumulation of coarse and rigid, but un-sintered, ash particles in the system. Co-gasification of MSS with sufficient amounts of cereal straw was found to be an effective way to mitigate these issues as well as eliminate thermal MSS drying requirements. Characterization of gas products and process performance showed that even though gas composition varied substantially, hot gas efficiencies of around 90% could be achieved for all MSS fuel types.